Pulmonary Arterial Hypertension in COPD and its Correlation with Disease Severity - Iftikhar Ali Kakar, Abdul Baqi, Nasir Azim, Hafsa Rafiq, Iqra Lodhi, Khalid Shahab, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pulmonary arterial hypertension is a condition that develops in advanced stages of chronic obstructive pulmonary disease. The development of pulmonary arterial hypertension indicate poor prognosis. Objective: To assess the arterial hypertension in COPD and its correlation with disease severity Methodology: This descriptive study was carried out at the Pulmonology department, Fatima Jinnah Institute of Chest Diseases and Sheikh Khalifa Bin Zayyed Al Nahyan Medical Complex Quetta from December 2021 to May 2022. The severity of COPD was measured by FEV1 (spirometry). All the data was collected by using a pre-designed proforma. The data was analyzed via SPSS version 24. Results: In this study, totally 80 patients were enrolled. The male participants in our study were 42 (52.5%) while female participants were 38 (48.5%). The overall frequency of pulmonary arterial hypertension in COPD was 28 (35%). There was a statistically significant positive association between the severity of COPD and presence of pulmonary arterial hypertension (p=0.038). Conclusion: Our study concludes that the most common complication of COPD is pulmonary arterial hypertension and should be investigated particularly in patients with advanced (severe and very severe) COPD in order to reduce the morbidity and mortality. Keywords: Prevalence, Pulmonary arterial Hypertension, Chronic obstructive pneumonic disease